Informative index for investment based on Kelly criterion. Issue 8 (3rd August 2022) - Wu, Mu-En; Syu, Jia-Hao; Srivastava, Gautam; Lin, Jerry Chun-Wei
ABSTRACT: When it comes to asset allocation and portfolio management, Kelly criterion is a mathematical formula used to optimise expected log-returns over the long term. Nonetheless, not all stocks are well suited for analysis using Kelly criterion, due to their transient nature and noisy data. This paper presents an innovative index by which to assess the suitability of stocks for analysis using the Kelly criterion. When applied to real-world stock data, the correlation coefficient between the proposed KSI and log-returns based on the Kelly criterion was − 57.045 % with a p -value of 1.215 × 10 − 1 . In a robustness test based on the Mid-Cap 100 dataset, the correlation coefficient was − 44.064 % with a p -value of 2.438 × 10 − 5 . The results demonstrate the efficacy of the KSI for portfolio management.